Efektivitas Dakwah Melalui Penggunaan Bahasa Sunda pada Pengajian di Masjid Darussalam Wanaraja Garut - Dahlia, Siti; Huriani, Yeni; AlBustomi, Ahmad Gibson (Polyscopia, 2025)
Da'wah serves as a crucial medium for disseminating and acquiring religious knowledge within the community. Effective da'wah requires preachers to adopt appropriate communication strategies that align with the linguistic and cognitive abilities of the audience, ensuring successful message reception and implementation. Sundanese is one of the languages commonly used by preachers in certain regions, particularly in social and religious interactions. This study employs a qualitative descriptive approach, utilizing observation, interviews, and documentation as data collection methods. The research focuses on evaluating the effectiveness of delivering da'wah in Sundanese within the Wanaraja Garut area. The findings indicate that preaching in Sundanese proves to be highly effective among the Sundanese community. It not only facilitates better understanding but also reinforces cultural identity, preserving traditional values that are gradually fading. The use of Sundanese in da'wah contributes to reviving traditional etiquette, such as respectful speech towards elders and politeness in social interactions. This study highlights the significance of language as a cultural and religious tool in sustaining both Islamic teachings and Sundanese traditions.